Keefektifan Model Project Based Learning Berbantu Media Replika Sistem Pencernaan Manusia Terhadap High Order Thinking Skills Siswa Kelas V SD Negeri 1 Ngasem Jepara - Pratiwi, Tri Ajeng; Wardana, M. Yusuf Setia; Purnamasari, Iin (CV. Supernova Office Stationary and Printing, 2023)
The background that prompted this research was students' high-level thinking skills which were low in science subjects. This is because the learning process is still teacher-centered so that students are less active when learning takes place and the model used by the teacher is not effective and does not use learning media. This study aims to find out how effective the Project Based Learning model is with the help of Replica Media of the Human Digestive System on High Order Thinking Skills for fifth grade students at SD Negeri 1 Ngasem. This research is a quantitative study using a Pre-Experimental Design and the type of type used is the One-Group Pretest-Posttest Design. The population in this study were 25 students of class V SD Negeri 1 Ngasem. The sampling technique taken is non-probability sampling, namely saturated sampling. Data collection techniques in this study were tests, observation and documentation. The results showed that the percentage of posttest classical learning completeness reached 84% with an average posttest score of 74.96 and an average pretest score of 51.2. For the calculation of the t-test for one sample between the pretest and posttest value data, a tcount of 12.37307 is obtained and a ttable of 2.06. Thus, Ho is rejected and Ha is accepted, meaning that the Project Based Learning learning model assisted by replica media of the human digestive system is effective against High Order Thinking Skills for fifth grade students at SD Negeri Ngasem.